Pelatihan Edukasi Dampak Positif Dan Negatif Interaksi Media Sosial Terhadap Remaja Di SMK Muhammadiyah Bangunjiwo - Sari Miranda, Bella Okta; Dahlan, Khoirul Anam; Annafii, Moch. Nasheh; Yudhana, Anton; Umar, Rusydi (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
In this dynamic technological era, changes permeate various aspects of life. Technology accelerates the shift towards the digital realm, with social media becoming the primary platform facilitating rapid interaction. However, its impact on psychological well-being and communication patterns is not always positive. To address this, an educational training program has been developed to provide adolescents with a deep understanding of the positive use of social media and how to manage its negative effects. The training takes place over one day at SMK Muhammadiyah Bangunjiwo, involving 30 students from grades 11 and 12. The methods include presentations, discussions, and interactive sessions. Survey results show that most students spend considerable time on social media, but they also recognize the importance of understanding its positive and negative impacts. This training successfully increases students' awareness of responsible social media usage, and it is hoped that similar activities can be conducted sustainably. The results indicate that with better understanding, students can optimize the use of social media to support learning and other activities, as well as develop positive character traits. This program contributes to shaping wise and responsible attitudes toward technology use among the younger generation. Awareness of the importance of digital literacy is also increasing, as evidenced by the post-test literacy index increasing by 0.49 compared to the Indonesian average in 2022.